1972
DOI: 10.1190/1.1440305
|View full text |Cite
|
Sign up to set email alerts
|

8‐hz Telluric and Magnetotelluric Prospecting

Abstract: Telluric and magnetotelluric surveys utilizing natural 8‐hz electromagnetic fields have detected resistivity variations associated with some proven sulfide deposits. From an operational point of view the telluric method is preferred to magnetotellurics. Either method, however, can detect a conducting dike, providing that its width is greater than its depth of burial. For surveys where the telluric field is measured in a direction perpendicular to the strike of the conductor, theoretical profiles derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1973
1973
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 3 publications
0
7
0
1
Order By: Relevance
“…Although the method is we11 known in the field of electrical engineering, the inception of its appIication to the earth's EM problems was first made by DuIaney and Madden ( 1962). Since then, many papers have been published on the use of the method to various geophysical problems (Swift 1967, Madden and Swift 1969, Slankis 1970, Swift 1971, Vozoff 1971, Slankis et al 1972.…”
Section: Introductionmentioning
confidence: 99%
“…Although the method is we11 known in the field of electrical engineering, the inception of its appIication to the earth's EM problems was first made by DuIaney and Madden ( 1962). Since then, many papers have been published on the use of the method to various geophysical problems (Swift 1967, Madden and Swift 1969, Slankis 1970, Swift 1971, Vozoff 1971, Slankis et al 1972.…”
Section: Introductionmentioning
confidence: 99%
“…Coils with cores of high permeability are generally used to detect the magnetic field components. It is only recently that the magnetotelluric method has been used with ELF sources (Slankis et al 1972;Strangway et al 1973). A natural-field ELF method called AFMAG (Audio Frequency Magnetics) has been used in both air-borne and ground-based surveys (Ward 1967).…”
Section: Existing Elf and Vlf Exploration Methodsmentioning
confidence: 98%
“…After a few attempts to test the applicability of the telluric method in geothermal areas (e.g., Beyer, 1977), it was concluded that the conductivity anomalies did not lend themselves to quantitative interpretation (Goldstein, 1988). Slankis et al (1972) reported 8 Hz telluric measurements made in the vicinity of heavy sulfide deposits. Relative resistivity measurements, obtained by comparison of telluric amplitudes, revealed the location of conductive sulfide bodies, provided that width was greater than depth of burial.…”
Section: Extraction Of the Ip Responsementioning
confidence: 97%